2021
DOI: 10.2174/0929867328666210628144347
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Synthesis and Biological Activities of Nonactic Acid and Its Derivatives

Abstract: : Nonactic acid, which is a macrocyclic nonactin subunit, contains four asymmetric centers and has the molecular formula of C10H18O3. Due to their various biological activities and challenging structural characteristics, nonactic acid and its derivatives have attracted much attention from scientists since 1955. These compounds possess significant antibacterial, insecticidal and acaricidal activities, as well as a promoting effect on plant growth. However, the studies in the anticancer activities of these compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Macrotetralids, including nonactin, are membrane-active compounds that violate the permeability of the membranes, particularly blocking the activity of potassium channels and inducing disturbance to the transport of ions into cells [ 11 , 25 , 52 ]. As a consequence, violation of oxidative phosphorylation, ATP hydrolysis, swelling of mitochondria, lysis of zoospores and other toxic effects were observed [ 11 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrotetralids, including nonactin, are membrane-active compounds that violate the permeability of the membranes, particularly blocking the activity of potassium channels and inducing disturbance to the transport of ions into cells [ 11 , 25 , 52 ]. As a consequence, violation of oxidative phosphorylation, ATP hydrolysis, swelling of mitochondria, lysis of zoospores and other toxic effects were observed [ 11 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonactin is a biologically active compound produced by several Streptomyces species [ 20 , 21 , 22 , 23 ], and is known as the macrotetrolide antibiotic consisting of four subunits in the form of nonactic acid [ 24 , 25 ]. Nonactic acid and/or its derivatives (monactin, dinactin, trinactin and tetranactin) possess antibacterial, antifungal, insecticidal and acaricidal activity [ 11 , 25 , 26 , 27 ]. It was also shown that Streptomyces globisporus produced nonactine and possessed insecticidal activity against Colorado potato beetle (Leptinotarsa decemlineata) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%